Competências necessárias para adequação e implantação do SPED: a percepção das organizações prestadoras de serviços contábeis de Fortaleza. - Guerra, Fellipe Matos (2015)
Interest in the subject about the skills needed for adaptation and implementation organizations to Public Digital Bookkeeping System (SPED): perception of organizations providing financial services to Fortaleza is justified in helping to raise awareness about the risks and opportunities for organizations providers of financial services. The context of the problematic reference to the following question: what level of compatibility between the skills necessary for the effective implementation of SPED design and expertise in the Fortress of accounting firms? The proposed overall objective is to analyze the compatibility of this professional expertise in accounting offices in Fortaleza and skills needed for effective implementation of the Public Digital Bookkeeping System (SPED).The methodology is based on an exploratory, descriptive and qualitative study; and the field survey of a sample of 10 companies providing financial services in the city of Fortaleza. The structure of this dissertation comprises information technology, history and evolution of the accounting system; the impact of the introduction of digital technology, the SPED, the accounting professional, personal and professional competence and service providers The main results show the light of certain objectives.